2020
DOI: 10.3390/catal10050513
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Ru Supported on Ni Nanowires for Low-Temperature Carbon Dioxide Methanation

Abstract: In this study, we investigated the catalytic performance of Ru nanoparticles (NPs) supported on Ni-nanowires for the first time. This appears to be a highly efficient catalyst for low-temperature methanation, e.g., ca. 100% conversion and 100% of CH4 selectivity can be achieved at ca. 179 °C, while the turnover frequency (TOF) value was 2479.2 h−1. At the same time, the onset of a reaction was observed at a temperature as low as 130 °C. The comparison of nano-Pd and nano-Ru supported on Ni-nanowires enabled us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The prepared catalyst exhibited a greatly enhanced lowtemperature activity with about 100% CO 2 conversion being achieved at a temperature as low as 200 • C. Carbon deposition was shown to deactivate the catalyst over time, with the initial activity being regained upon treatment under H 2 atmosphere. In a followup work, Siudyga et al [110] synthesized 1.5% Ru catalysts supported on Ni nanowires via a similar preparation method. The higher surface area of the 1D nanostructure of the Ni support provided an additional advantage, with around 100% CO 2 conversion being reached at 179 • C and the onset temperature for the reaction being observed at just 130 • C. Siudyga et al [111] also observed that Ru/Ni catalysts are highly active for CO methanation from syngas, with 100% CO conversion being reached at 178 • C and observable CO conversion being detected even at −7 • C.…”
Section: Promotion With Rhmentioning
confidence: 99%
“…The prepared catalyst exhibited a greatly enhanced lowtemperature activity with about 100% CO 2 conversion being achieved at a temperature as low as 200 • C. Carbon deposition was shown to deactivate the catalyst over time, with the initial activity being regained upon treatment under H 2 atmosphere. In a followup work, Siudyga et al [110] synthesized 1.5% Ru catalysts supported on Ni nanowires via a similar preparation method. The higher surface area of the 1D nanostructure of the Ni support provided an additional advantage, with around 100% CO 2 conversion being reached at 179 • C and the onset temperature for the reaction being observed at just 130 • C. Siudyga et al [111] also observed that Ru/Ni catalysts are highly active for CO methanation from syngas, with 100% CO conversion being reached at 178 • C and observable CO conversion being detected even at −7 • C.…”
Section: Promotion With Rhmentioning
confidence: 99%
“…They can also easily get deactivated at high temperatures by sintering and/or coke deposition and are particularly susceptible to sulfur poisoning, e.g., from H 2 S [80,91,97]. There are several solutions that can improve the performance and life span of this type of catalyst, for instance, using a support [83,91,[98][99][100], catalytic promoters [91,99,100], coupling with other non-noble elements into alloys or spinel structures [100,101], or composing bimetallics with noble metals [10,53,[74][75][76]84]. Ruthenium is one of the most used noble metals for this purpose.…”
Section: Ru/ni Catalysts For Low-temperature Co 2 (Co) Methanationmentioning
confidence: 99%
“…Ru/Ni conjugate appeared highly active at low temperature (entry 6 in Table 3) [53]. Interestingly, a special method for preparing a catalyst produces an unalloyed bimetallic construct [38,53,75,108].…”
Section: Ru/ni Catalysts For Low-temperature Co 2 (Co) Methanationmentioning
confidence: 99%
See 2 more Smart Citations